2019
DOI: 10.13075/ijomeh.1896.01320
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining the effectiveness of conservative treatment in patients with carpal tunnel syndrome

Abstract: Objectives: The study aims to assess selected factors contributing to the long-term effects of the conservative treatment of carpal tunnel syndrome (CTS). Material and Methods: Forty-nine individuals diagnosed with CTS were enrolled in the study. The symptoms resulted from occupational hand overuse in 37 patients. The assessment involved 78 hands before the therapy (study 1) and 1 year after the end of the therapy (study 2). The clinical symptoms assessed included: pain, numbness, tingling, morning stiffness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Our results demonstrated that SNCV is an independent prognostic factor of outcome, where a worse SNCV score predicts poor outcomes for patients after the D5W injection. This finding was in line with previous research [20][21][22][23] and this information can be valuable for clinical practice of decision making and informs patient expectations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results demonstrated that SNCV is an independent prognostic factor of outcome, where a worse SNCV score predicts poor outcomes for patients after the D5W injection. This finding was in line with previous research [20][21][22][23] and this information can be valuable for clinical practice of decision making and informs patient expectations.…”
Section: Discussionsupporting
confidence: 91%
“…Visser et al [20] stated that only severity of electrodiagnostic results was a predictor of outcome after corticosteroid injections and a mild grade has a better outcome. Zwolińska et al [21] reported that worse primary SNCV and DML are prognostic factors of a less favorable outcome after conservative treatment such as whirlpool massage, sonotherapy, and glide exercise. Moreover, CTS patients with better DML and sensory latencies were good candidates for wrist splinting [22], and failure of wrist splinting and corticosteroid injections could be predicted by long motor and sensory distal latency [23].…”
Section: Discussionmentioning
confidence: 99%
“…We measured patients' satisfaction only at 6 months after CTS surgery. However, studies with longer follow-up periods showed that the persistence of positive effects had no further improvement beyond 6 months [4,17,18]. Furthermore, there was a substantial drop-out rate among patients between the intake and the follow-up at 6 months.…”
Section: Strength and Limitationsmentioning
confidence: 99%
“…Electrophysiological studies are the most objective way of assessing a CTS diagnosis or grading, 19,20 and it may be widely used as a prognostic tool. Poor initial electrodiagnostic results were considered predictors of poor outcomes in conservative treatment, 27 and electrodiagnostically mild CTS was related to good outcomes in steroid injection. 28 However, few studies found no association between electrophysiological studies and outcomes after steroid injection.…”
Section: Discussionmentioning
confidence: 99%
“…Although younger age was shown to be an independent predictor of higher postoperative satisfaction, 49,50 one study revealed that old age was a good outcome predictor after conservative treatment. 27 Bowman et al 51 reported that sex and the dominant hand were outcome predictors when treating CTS, in which males and the dominant hand had poor outcomes. Although older age, shorter symptom duration, and higher VAS score were noted in good outcome group in our study, none of them were associated with outcome significantly.…”
Section: Although Other Characteristics Have Been Reported As Predictorsmentioning
confidence: 99%